The retinal "lozenge" or "dull macular reflex" in Alport syndrome may be associated with a severe retinopathy and early-onset renal failure. Issue 3 (19th November 2008) - Colville, D; Wang, Y Y; Tan, R; Savige, J
Abstract : Background and aims: Alport syndrome is an inherited disease with renal failure, and often a hearing loss, lenticonus and dot-and-fleck retinopathy. A retinal "lozenge" or "dull macular reflex" has been described in some patients. This study determined the prevalence and significance of this sign. Methods: Twenty-three patients from 14 families with X linked Alport syndrome and seven from four families with autosomal recessive disease underwent slit-lamp biomicroscopy for lenticonus, direct and indirect ophthalmoscopy, and photography for the retinopathy. Results: The lozenge was present in five males (38%) but no females with X linked Alport syndrome, as well as one individual with recessive disease (1/7, 14%). It resulted from the sharp demarcation between the normal fovea and a perifoveal annnulus of confluent dots and flecks that were obvious with magnification of retinal photographs. The lozenge was first noted in adolescence and was always associated with early-onset renal failure, hearing loss and lenticonus. Conclusion: Clinicians must be aware that the "lozenge" or "dull macular reflex" described in Alport syndrome is not a normal variant but reflects a severe, almost confluent perimacular dot and fleck retinopathy. This sign is useful diagnostically and also prognostically, since it is associated with early-onset renal failure.